Performance of Microfinance Investment Funds - Gergeshelidze, Nino; Zárybnická Žárová, Marcela, 1959-; Rýdlová, Barbora, 1976-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This dissertation examines the performance of MFIFs in terms of portfolio diversification and their attractiveness to investors. These funds are the main providers of financial services to MFIs. To assess the resilience of the funds to economic uncertainty, the historical performance per annum of microfinance investment funds is analyzed from 2015 to 2023, including the COVID-19 pandemic period. The data consists of 130 funds, which are either fixed-income funds or mixed-allocation funds. All of them are open-end funds. This study employs the CAPM regression to assess if microfinance investment funds contribute to the investor's portfolio diversification, using risk-adjusted performance measures like Sharpe ratio, Jensen’s alpha, and Treynor ratio and risk measures like the beta coefficient, the standard deviation of returns, and R2. Moreover, a matched pair analysis compares the performance of microfinance investment funds with other socially responsible funds in terms of risk and return. The analysis revealed that microfinance investment funds offer valuable diversification benefits to investors. The findings of this dissertation are in line with the previous research. Close to zero beta indicates a low correlation with benchmark indices and lower volatility compared to the developed and developing markets. This may suggest potential diversification benefits of the MFIFs. Positive Jensen’s alpha, for many funds, indicates the outperformance of these funds, while negative alphas may be due to their focus on social impact rather than poor financial performance. The Sharpe ratio of individual funds varies significantly; the majority of the funds have positive Sharpe ratios. However, in which fund to invest should be evaluated with cautios by potential investors. The portfolios’ Sharpe ratio showed that investing in microfinance funds does not worsen the risk-adjusted returns of the investors; in fact, it could be beneficial.
Matched pair analysis confirmed that MFIFs provide better diversification benefits than SRIs. As a result, SRIs have a higher market correlation. MFIFs have better risk-adjusted returns. Furthermore, the performance analyses per annum showed that MFIFs had a stable performance during COVID-19 and were resilient during market shakes compared to their benchmark indexes.
Vedoucí práce: Marcela Zárybnická Žárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses